2018
DOI: 10.1021/acs.jafc.8b00210
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Xylan Oligosaccharide Utilization Systems in Pediococcus acidilactici Strain BCC-1

Abstract: Xylan oligosaccharides (XOS) are the hydrolysates of xylan. To compare the proliferation effect of XOS, glucose, fructo oligosaccharides (FOS), xylose, XOS, and a media without carbohydrate source (control) on Pediococcus acidilactici strain BCC-1, the de novo sequencing of Pediococcus acidilactici strain BCC-1 was conducted, and the underlying mechanism of prebiotic xylo oligosaccharide between xylose and XOS was revealed through transcriptomic analysis. Compared to FOS, glucose, and xylose, XOS exhibits a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Therefore, decreased concentrations of 3hydroxy-3-methylglutaric acid and succinate tend to prevent inflammation and maintain the gut health of broilers. Our previous study has been demonstrated P. acidilactici BCC-1 can effectively use xylose as an energy source (Lei et al, 2018) and other study found some Pediococcus acidilactici strains could utilize D-arabitol (Wang et al, 2019). Also, some Pediococcus species such as Pediococcus parvulus can effectively use sorbitol (Pérez-Ramos et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, decreased concentrations of 3hydroxy-3-methylglutaric acid and succinate tend to prevent inflammation and maintain the gut health of broilers. Our previous study has been demonstrated P. acidilactici BCC-1 can effectively use xylose as an energy source (Lei et al, 2018) and other study found some Pediococcus acidilactici strains could utilize D-arabitol (Wang et al, 2019). Also, some Pediococcus species such as Pediococcus parvulus can effectively use sorbitol (Pérez-Ramos et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…XOS (extracted from corncob, 95% purity, DP of 2-7 and containing 95.6% XOS, 2.4% xylose, 1.4% glucose, 0.5% arabinose, and 0.1% raffinose) was obtained from Shandong LongLive Biotechnology (DeZhou, Shandong, China). P. acidilactici BCC-1 was isolated from the cecum of 36-day-old broiler without feeding any antibiotics (Lei et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance, prophages, plasmid and plasmid-associated bacteriocins have been indicated as source of variability at P. pentosaceus genomes 9 . Our P. acidilactici strain, however, also contains a plasmidassociated bacteriocin operon (pediocin PA-1), differing from other strains reported in the literature, such as ZPA017 and BCC-1 10,11 . The metabolic characteristics of the strains obtained indicated a wider metabolic potential for carbohydrate transport for the P. acidilactii transport while the P. pentosaceus presented he capability to synthesize lysine and had quorum sensing related genes.…”
Section: Discussionmentioning
confidence: 56%
“…Based on the pangenomes of our isolates against reference genomes, we propose P. pentosaceus ST31BZ as a new strain of P. acidilactici and strains ST75BZ and ST87BZ as a new strain of P. pentosaceus. The two closest strains to P. acidilactici were ZPA017 and BCC-1, isolated from feces of a healthy pig 10 and cecum of a broiler chicken 11 , respectively. The unique genes present in our isolates were related to antibiotic resistance and prophages, such as glycopeptide antibiotics resistance protein (COG4767) and phage portal protein BeeE (COG4695) in P. acidilactici ST31BZ (Supplementary Table 3); and ABC-type multidrug transport system (COG0842) and phage terminase large subunit (COG1783) in P. pentosaceus ST75BZ and ST87BZ.…”
Section: Pangenomic Analysis Of Pediococcus Sppmentioning
confidence: 99%